Research on the efficient training methods of diving skills of walking on the springboard of junior divers - Wu, H. (Sport Science and Technology, 2012)
Based on years of practice experience of exercise training, in connection with the characteristic of diving skills of walking on the springboard ,and considering the junior diver's characteristics of mind and body, this paper puts forwards efficient strategy for training methods of diving skill.